The Impact of Food Specific IgG Antibodies on Migraine and Its Comorbidities - Zhi‐Ming Zhao; Mei‐Mei Yang; Xian‐Shu Zhao; Fu‐Jun Wan; Bao‐Li Ning; Li‐Ming Zhang; Jun Fu (Immunity, Inflammation and Disease)
ABSTRACT Objective To investigate the differences in headache and comorbidity symptoms between migraine patients with negative and positive food specific IgG antibodies, and explore the correlation between these symptoms with food specific IgG antibodies. Methods A total of 129 migraine patients were enrolled. Seven questionnaires were used to gather information regarding the symptoms of migraine, gastrointestinal, depression, anxiety, and sleep. Serum specific IgG antibodies against 14 kinds of food were detected using enzyme‐linked immunosorbent assays. Results Patients with migraine diagnosis who had positive food specific IgG antibodies had significantly worse headaches, gastrointestinal and anxiety symptoms, compared to the patients with negative IgG antibodies. Patients with more IgG positive foods and higher total positive IgG concentration generally had worse migraine conditions, anxiety, depression, and gastrointestinal symptoms. Conclusion The effect of food specific IgG antibodies on severity of migraine and its comorbidities were antibody‐quantity and IgG‐concentration dependent. Future studies are warranted to explore the mechanism underlying such relationship.